An educational setup for a Laser Induced Breakdown Spectroscopy (LIBS) system and its usage for the characterization of cultural heritage objects - Sianoudis, Ioannis; Hein, Anno; Mitsou, Giorgos; Chatzidakis, Maria; Drakaki, Eleni (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2010)
<span style="font-size: 11pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">An experimental setup for laser induced breakdown spectroscopy (LIBS) has been developed for educational purposes, to be used in the physics curriculum of science students and of students who are specializing in the field of cultural heritage. The setup comprises basically a Q-switched Nd:YAG laser and a fiber optic spectrometer. All components were already existing equipment at the physics laboratories at the TEI of Athens, so that they could be assembled in-house to a considerably economic LIBS setup. The proposed laboratory exercises are focused on one hand on imparting the knowledge about physical principles and phenomena associated with the creation of plasma and the radiation processes, while on the other hand, the students will be trained in the operation and handling the actual analytical process, in terms of specific applications. Various parameters are examined, concerning the laser-matter interaction and the process issues, such as calibration, interpretation of spectra and evaluation of results. Exemplary measurements as an autonomous learning and teaching module were implemented, demonstrating the qualitative and quantitative analysis of various materials typically associated with cultural heritage objects, such as metal standards and original objects and replicas of mural paintings.